Deposits of minerals of the Kirovograd ore region of the Ukrainian shield: connection with the deep process - O.V. Usenko (Геофизический журнал, 2013)
Conditions of magmatic rocks complexes and mineral deposits formation of the central part of the Ingul block are determined by existence of two melting sources in the mantle and the crust as well as by the deep permeable «transform» zone - tectonic suture Kherson-Smolensk. Along the deep transform zone supply of the mantle source by melts and fluids is realized and the existence of the crust source provides mixing of earlier melts with new portions added from the mantle. Changing of composition of the deep fluid as well as its transformation in the melts of both sources of melting causes the composition of deposits produced near the surface. Production of quarts gold ore veins is related to water chloride-potassium fluids accompanying formation of palingenetic Kirovograd granites. Increase of fluid alkalinity in the mantle source predetermines activity of the elements which are able to be brought to melt in alkaline environment - titanium and uranium. Gradual dilution of residual crust melts with fluoride-sodium fluid leads to appearance of lithium pegmatite with rare metal mineralization. Accumulation of Li, Сs, Ве, Nb et al. is related to changing of distribution coefficients between solid phases and granite melt in presence of fluorine. During the process of Korsun-Novomirgorod pluton and albitite formation, alkalinity of deep fluid increases. In the crustal source its dilution by water takes place that leads to decrease of alkalinity and increase of oxidation potential. Deposition of brannerite and uranium oxides becomes possible.